2010
DOI: 10.1016/j.addr.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based theranostic agents

Abstract: Theranostic nanomedicine is emerging as a promising therapeutic paradigm. It takes advantage of the high capacity of nanoplatforms to ferry cargo and loads onto them both imaging and therapeutic functions. The resulting nanosystems, capable of diagnosis, drug delivery and monitoring of therapeutic response, are expected to play a significant role in the dawning era of personalized medicine, and much research effort has been devoted toward that goal. A convenience in constructing such function-integrated agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
833
0
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,269 publications
(865 citation statements)
references
References 178 publications
(6 reference statements)
0
833
0
10
Order By: Relevance
“…Their well-developed surface chemistry makes it easy to load them with pharmaceutics and promote them to be theranostic nanosystems. 71,72 In vivo and in vitro MRI measurements showed that the contrast enhancement properties of the dendronized NPs were higher than those obtained with commercial polymer-coated NPs (Figure 3). 22 Figure 3: a) Synthetic scheme of NCDs, b) Spin echo T2 weighted axial images sequentially acquired before and after an injection of 650 µl of NCDs at 7T with a small animal dedicated MRI (Biospin -Brücker®).…”
Section: Performance Of Ncds In Bionanomedicine and As Nanocarriers Imentioning
confidence: 94%
“…Their well-developed surface chemistry makes it easy to load them with pharmaceutics and promote them to be theranostic nanosystems. 71,72 In vivo and in vitro MRI measurements showed that the contrast enhancement properties of the dendronized NPs were higher than those obtained with commercial polymer-coated NPs (Figure 3). 22 Figure 3: a) Synthetic scheme of NCDs, b) Spin echo T2 weighted axial images sequentially acquired before and after an injection of 650 µl of NCDs at 7T with a small animal dedicated MRI (Biospin -Brücker®).…”
Section: Performance Of Ncds In Bionanomedicine and As Nanocarriers Imentioning
confidence: 94%
“…Theranostic nanoparticles, which combine both therapeutic and diagnostic capabilities in one dose, have great promising in disease treatment [71,72]. GNRs have been developed as theranostic nanoparticles in several studies.…”
Section: Gnrs In Theranosticsmentioning
confidence: 99%
“…New materials and techniques are facilitating the production of various nano-particles suitable both as (targeted) imaging probe and drug carrier. Currently various types of nanoparticles are being investigated as versatile tools for theranostics purposes [26,27]. A major advantage of nanoparticles for theranostics would be the high payload of both therapeutic agent and imaging probe that can be delivered to the target tissue.…”
Section: Theranosticsmentioning
confidence: 99%